D COKERI NEW SUBGENUS AND SAN LUIS POTOSIECIES FROM THE CAVES OF THE VALLES SAN LUIS POTOSI REGION - TAFALL OSORIO, B F (Rockefeller Foundation, CD MEXICO, DF, MEX, 1944)
E claytonhoffi is described from "Cueva Chica," Pujal, San Luis Potosi E (Cytherites) heterodonta ssp sinuosa from the same location is also described
CIENC MEX
Keywords: D COKERI, NEW SUBGENUS, SPECIES, CAVES, VALLES, SAN LUIS POTOSI, REGION; MULTIDISCIPLINARIA; GEOLOGIA; GEOLOGIA REGIONAL